2010
DOI: 10.1002/adem.200900313
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Damage Detection With Acoustic Emission Analysis During Cyclic Loading of Wire Reinforced EN AW‐6082

Abstract: In the field of lightweight construction, hybrid structures such as reinforced metal matrix composites are highly qualified materials. The direct composite extrusion process allows for continuous manufacturing of wire reinforced aluminum matrix profiles. The aim is to increase the stiffness and specific strength in a way that the composite material shows better mechanical properties than the single matrix material. To determine and locate damage evolution during cyclic loading of spring steel reinforced EN AW‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Since the current work involves the comparison of the results achieved in several studies, [10][11][12][13][14][15][16][17] investigated composite materials (and their corresponding matrix materials) with their testing frequency and the testing machine actuator used. Figure 3 gives an overview of the S/N curves in double logarithmic scale for all investigated unreinforced materials and 11.1 vol% reinforced composites.…”
Section: Specimen Geometry and Experimental Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the current work involves the comparison of the results achieved in several studies, [10][11][12][13][14][15][16][17] investigated composite materials (and their corresponding matrix materials) with their testing frequency and the testing machine actuator used. Figure 3 gives an overview of the S/N curves in double logarithmic scale for all investigated unreinforced materials and 11.1 vol% reinforced composites.…”
Section: Specimen Geometry and Experimental Proceduresmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] It could be confirmed that the reinforcing element leads to a significant increase in lifetime, noticeable by a parallel shift of the regression lines of the S-N curves in double logarithmic scale. [10][11][12][13][14][15][16][17] It could be confirmed that the reinforcing element leads to a significant increase in lifetime, noticeable by a parallel shift of the regression lines of the S-N curves in double logarithmic scale.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations